2014
DOI: 10.1021/es500734n
|View full text |Cite
|
Sign up to set email alerts
|

Bacterially Produced Calcium Phosphate Nanobiominerals: Sorption Capacity, Site Preferences, and Stability of Captured Radionuclides

Abstract: A Serratia sp. bacterium manufactures amorphous calcium phosphate nanominerals (BHAP); this material has shown increased sorption capacity for divalent radionuclide capture. When heat-treated (≥450 °C) the cell biomass is removed and the biominerals are transformed to hydroxyapatite (HAP). Using a multimethod approach, we have elucidated both the site preferences and stability of analogue radionuclide incorporation for Sr, Co, Eu, and U. Strontium incorporates within the bulk amorphous inorganic phase of BHAP;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…The interactions of REEs with biogenic phosphates and specific transporter uptake are two recently disclosed processes having the potential to recover the REEs from aqueous waste streams. Firstly, the sorption on, or the encapsulation into the biogenic phosphate nano-minerals and the formation of REE-phosphate complexes were demonstrated using biofilms of Serratia strains [37,38]. Using an extremophile, acidophilic methanotrophic Methylacidiphilum fumariolicum, Pol et al [39] observed that the function of methanol dehydrogenase (MDH) in this bacterium strictly depends on the presence of REEs.…”
Section: Bio-reclamation Of Rare Earth Elementsmentioning
confidence: 99%
“…The interactions of REEs with biogenic phosphates and specific transporter uptake are two recently disclosed processes having the potential to recover the REEs from aqueous waste streams. Firstly, the sorption on, or the encapsulation into the biogenic phosphate nano-minerals and the formation of REE-phosphate complexes were demonstrated using biofilms of Serratia strains [37,38]. Using an extremophile, acidophilic methanotrophic Methylacidiphilum fumariolicum, Pol et al [39] observed that the function of methanol dehydrogenase (MDH) in this bacterium strictly depends on the presence of REEs.…”
Section: Bio-reclamation Of Rare Earth Elementsmentioning
confidence: 99%
“…Firstly, the sorption on, encapsulation into biogenic phosphate nanominerals and formation of REE-phosphates were demonstrated using biofilms of Serratia strains [63,64]. The formation of biogenic Ce phosphates was also shown to occur on the Mn-oxidizing bacteria Leptothrix and Pseudomonas [65].…”
Section: Microbe-metal Interactionsmentioning
confidence: 99%
“…The mechanism of bio-mineralization has been well-characterized in the γ-Proteobacteria Serratia sp. [145]. Uranium is trapped on the surface of the cell or in the extracellular matrix on material like EPS, extracellular polymeric substances (Figure 2.1).…”
Section: Mineralizationmentioning
confidence: 99%
“…The surface-complexed uranium, phosphate and often calcium react forming immobilized minerals [81] [82] [145]. In Serratia this is seen under fermentative growth and different minerals may be produced under phosphate limited conditions [82].…”
Section: Mineralizationmentioning
confidence: 99%